The Palgrave Handbook of International Energy Economics - Hafner, Manfred; Luciani, Giacomo (Springer Nature, 2022)
This open access handbook is distinguished by its emphasis on international energy, rather than domestic energy policies or international geopolitic aspects. Addressing key topics such as energy production and distribution, renewables and corporate energy structures, alongside global energy trends, regional case studies and emerging areas such as the digitalization of energy and energy transition, this handbook provides a major new contribution to the field of international energy economics. Written by academics, practitioners and policy-makers, this handbook is a valuable and timely addition to the literature on international energy economics. This book was published open access with the support of Eni.